2013
DOI: 10.1002/srin.201300271
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Quantification of the Austenite‐Stabilizing Effect of Mn in CrMnNi As‐Cast Stainless Steels

Abstract: In this study, the austenite-stabilizing effect of manganese in as-cast Fe-(12-16)Cr-(0-13) Mn-6Ni (concentrations in wt%) stainless steels was investigated by means of light optical microscopy (LOM) and magnetic scale measurements. The well known Schaeffler-diagram was used for the prediction of the microstructure at room temperature. Major deviations were observed between the Schaeffler-diagram predictions and the experimentally determined phase fractions. Manganese contents above 2% were found to stabilize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 11 publications
0
11
1
Order By: Relevance
“…The results revealed that the austenite stabilizing effect of Mn, and concomitantly the variation of martensite transformation temperatures (as quantified by the calculation of the Ni-equivalent, Ni eq ), is not constant but instead increases with increasing Cr eq . 49 This in turn also indicates that a change in Cr eq would further enhance the effect of Mn evaporation during EBM processing on the resulting mechanical response of additively manufactured specimens. This aspect should be taken into consideration for the development of future alloys tailored for AM.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results revealed that the austenite stabilizing effect of Mn, and concomitantly the variation of martensite transformation temperatures (as quantified by the calculation of the Ni-equivalent, Ni eq ), is not constant but instead increases with increasing Cr eq . 49 This in turn also indicates that a change in Cr eq would further enhance the effect of Mn evaporation during EBM processing on the resulting mechanical response of additively manufactured specimens. This aspect should be taken into consideration for the development of future alloys tailored for AM.…”
Section: Discussionmentioning
confidence: 99%
“…By focusing on the extreme, it has been demonstrated that chemical composition and properties can be tailored by proper process adjustment, e.g., when comparing batches II and V. Future work should focus on an expansion of the methodology and a maximization of the effects of element vaporization on the mechanical and thermodynamic properties. One approach could follow findings obtained for conventionally processed material published by Wendler et al 49 It was shown that an increased Cr fraction (or Cr-equivalent, Cr eq ) has an amplifying effect on the impact of Mn. The results revealed that the austenite stabilizing effect of Mn, and concomitantly the variation of martensite transformation temperatures (as quantified by the calculation of the Ni-equivalent, Ni eq ), is not constant but instead increases with increasing Cr eq .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[30] The chemical composition of the investigated material (Table I) is based on a patent specification for maximizing energy absorption by the TRIP effect. [31] The steel alloy was cast into sand dies with dimensions of 200 9 200 9 16 mm by ACTech GmbH, Freiberg, Germany.…”
Section: Methodsmentioning
confidence: 99%
“…This constitutional diagram was originally developed for the microstructure prediction subsequent to the welding of high-alloy steels [25]. Nevertheless, it may as well be used for the prediction of cast microstructures [26,27]. By means of the following Ni-and Cr-equivalent equations by Weiss et al [28], the austenite stability was calculated.…”
Section: Microstructure Of Cast Steels After Solution Annealingmentioning
confidence: 99%